2006
DOI: 10.1176/appi.ps.57.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Payments for Attendance at Appointments for Depression Among Low-Income African Americans

Abstract: Incentive payments have the potential to improve appointment adherence among low-income African Americans with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…Several of the studies reviewed above included incentives for treatment attendance as well as drug abstinence, with positive results (e.g., Helmus et al, 2003; Ries et al, 2004). In addition, Carey and Carey (1990) found positive effects of contingent incentives on attendance at a day treatment for SUD in 53 people with SMI, and Post et al (2006) found that incentives ($10 per appointment) increased therapy attendance and reduced appointment rescheduling among 50 people with depression during a 12-week active intervention period. Priebe et al (2009) recently described a randomized controlled trial aimed at investigating whether financial incentives contingent upon depot antipsychotic medication adherence, compared to treatment as usual, improve clinical and psychosocial functioning among non-adherent patients with psychotic disorders.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several of the studies reviewed above included incentives for treatment attendance as well as drug abstinence, with positive results (e.g., Helmus et al, 2003; Ries et al, 2004). In addition, Carey and Carey (1990) found positive effects of contingent incentives on attendance at a day treatment for SUD in 53 people with SMI, and Post et al (2006) found that incentives ($10 per appointment) increased therapy attendance and reduced appointment rescheduling among 50 people with depression during a 12-week active intervention period. Priebe et al (2009) recently described a randomized controlled trial aimed at investigating whether financial incentives contingent upon depot antipsychotic medication adherence, compared to treatment as usual, improve clinical and psychosocial functioning among non-adherent patients with psychotic disorders.…”
Section: Future Directionsmentioning
confidence: 99%
“…33 tested the hypothesis that attendance at a day treatment programme could be increased by offering small incentives to patients with mental illness and substance abuse and found a modest increase in attendance over time. In 2006, Post and colleagues 34 examined the attendance of 50 low-income African Americans with depression at therapy appointments without incentives for 12 weeks, followed by tracking 12 weeks during which US$10 payments were given at regular appointments. They found patients had better adherence when payments were attached to appointments.…”
Section: Financial Incentive Researchmentioning
confidence: 99%
“…Die Hepatitis b-Impfraten unter Obdachlosen konnten durch die Gewährung von $20 pro Monat (über sechs Monate hinweg) von 23% auf 69% verbessert werden, und waren daher wesentlich effektiver als traditionelle Methoden der Information und Aufklärung [26]. Post et al zeigten, dass bei afro-amerikanischen Patienten mit Depressionen die Gewäh-rung von $10 für jeden wahrgenommenen Therapietermin die Raten von 69% auf 86% verbesserten [27].…”
Section: Evidenz: Gesundheitsverbesserungunclassified